Anti-Neuroinflammatory Potential of Polyphenols by Inhibiting NF-ΚB to Halt Alzheimer's Disease - Uddin, Md. S.; Hasana, Sharifa; Ahmad, Jamil; Hossain, Md. Farhad; Rahman, Md. Mosiqur; Behl, Tapan; Rauf, Abdur; Ahmad, Ausaf; Hafeez, Abdul; Perveen, Asma; Ashraf, Ghulam Md (Current Pharmaceutical Design, 2021)
Alzheimer's disease (AD) is an irrevocable chronic brain disorder featured by neuronal loss, microglial accumulation, and progressive cognitive impairment. The proper pathophysiology of this life-threatening disorder is not completely understood and no exact remedies have been found yet. Over the last few decades, research on AD has mainly highlighted pathomechanisms linked to a couple of the major pathological hallmarks, including extracellular senile plaques made of amyloid-β (Aβ) peptides, and intracellular neurofibrillary tangles (NFTs) made of tau proteins. Aβ can induce apoptosis, trigger an inflammatory response, and inhibit the synaptic plasticity of the hippocampus, which ultimately contributes to reducing cognitive functions and memory impairment. Recently, a third disease hallmark, the neuroinflammatory reaction that is mediated by cerebral innate immune cells, has become a spotlight in the current research area, assured by pre-clinical, clinical, and genetic investigations. Nuclear factor kappa-light-chain-enhancer of activated B cells (NF-ΚB), a cytokine producer, is significantly associated with physiological inflammatory proceedings and thus shows a promising candidate for inflammation- based AD therapy. Recent data reveal that phytochemicals, mainly polyphenol compounds, exhibit potential neuroprotective functions and these may be considered as a vital resource for discovering several drug candidates against AD. Interestingly, phytochemicals can easily interfere with the signaling pathway of NF-ΚB. This review represents the anti-neuroinflammatory potential of polyphenols as inhibitors of NF-ΚB to combat AD pathogenesis.
Keywords: Polyphenols